HARDENING BY HARD CHROMING (ELECTROLYTIC) - STĂNCIOIU A; STĂNCIOIU E.L. (Fiabilitate şi Durabilitate, 2023)
The deposition of a layer of chrome on the surface of a part, through hard (electrolytic) chrome plating, is applied in order to increase the hardness and wear resistance of the surface layer of the working surfaces of the active elements of the punch. At the same time, the purpose of this procedure is to restore the dimensions of the active elements, worn, during exploitation